Physical exercise as add-on treatment in adults with ADHD – the START study: a randomized controlled trial - Svedell, Lena Axelsson; Lindvall, Mialinn Arvidsson; Holmqvist, Kajsa Lidström; Cao, Yang; Msghina, Mussie (Frontiers in Psychiatry, 2025)
Adult ADHD is associated with various health challenges and reduced quality of life. Current guidelines recommend multimodal treatment, and physical exercise has emerged as a promising non-pharmacological alternative, although evidence from randomized controlled trials remains limited. In this randomized controlled trial, we aimed to assess the clinical effectiveness of physical exercise as an add-on treatment for adults with ADHD compared to treatment as usual. The trial included adults with a clinically confirmed diagnosis of ADHD was conducted at one Psychiatric clinic in Sweden. Participants were randomly assigned (2:1, no stratification) using an electronic case-report platform, to either physical exercise (the protocolized 12-week intervention START) or treatment as usual (local community care). Primary outcome was the ASRS-v1.1 Symptom checklist at 12 weeks after inclusion. The analysis followed a modified intention-to-treat principle, excluding participants who provided no data beyond baseline. Of the 63 participants enrolled, 43 were randomly assigned to START physical exercise intervention and 20 to treatment as usual. After accounting for withdrawals (n = 11) and loss to follow up (n = 11), the primary analysis included data from 41 participants (30 assigned to START intervention and 11 to treatment as usual). The START intervention resulted in improved ADHD symptoms after 12 weeks, as measured by ASRS-v1.1. Symptom improvement differed significantly between groups (mean difference -6.98, 95% CI: -12.30 to -1.65; p = 0.012) with an effect size of 0.93 favoring the intervention group. No serious adverse events were reported. The results suggest that physical exercise may be a feasible, safe and clinically meaningful complement to standard care for adults with ADHD. However, the findings should be interpreted in the light of potential confounders and methodological limitations. This trial is registered with the ClinicalTrials.gov. Date of registration: 2021-05-14.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05049239, identifier NCT05049239.